The utility of whole exome sequencing in diagnosing neurological disorders in adults from a highly consanguineous population. (2nd January 2019) - Mu, Weiyi; Schiess, Nicoline; Orthmann-Murphy, Jennifer L.; El-Hattab, Ayman W.
Abstract: There is increasing evidence that whole exome sequencing (WES) has a high diagnostic yield and is cost-efficient for individuals with neurological phenotypes. However, there is limited data on the use of WES in non-Western populations, including populations with a high rate of consanguinity. Retrospective chart review was performed on 24 adults with undiagnosed neurological symptoms evaluated in genetics and neurology clinics in a tertiary care facility on the Arabian Peninsula, and had WES between 2014 and 2016. Definitive diagnoses were made in 13/24 (54%) of cases. Of these, 5/13 (38%) revealed novel pathogenic variants. Of the known 19/24 (79%) consanguineous cases, diagnostic rate was slightly higher, 11/19 (58%) as compared to 2/5 (40%) among non-consanguineous cases. Autosomal recessive disorders comprised 10/13 (77%) of molecular diagnoses, all found to be due to homozygous pathogenic variants among consanguineous cases. WES in this cohort of adults with neurological symptoms had a high diagnostic rate likely due to high consanguinity rates in this population, as evidenced by the high diagnostic rate of homozygous pathogenic variants.